Minimum inhibition concentration of two antibiotics and 1 two plants extract against Mycoplasma galisepticum in 2 Iraq - Khalid Mohammed, Ansam; Abd-Al-Kareem Abd-Al-Shaheed, Dalia (International Journal of Psychosocial Rehabilitation, 2024)
This study was designed in order to evaluate the effectives of two antibiotics and two 9plant extracts against Mycoplasma galisepticum. Two commercial antibiotics 10tilmicosin and enrofloxacin used for minimum inhibition concentration detection 11against Mycoplasma galisepticum isolates. Two plants extracts also used for the same 12purpose which is garlic and thyme. Using the micro-broth technique to determine the 13growth of in vitro activities of tilmicosin, enrofloxacin, garlic and thyme against the 14isolates of Mycoplasma gallisepticum. The results showed that the tilmicosin had 15MICs of 7.8 mg/ml. while, enrofloxacin showed the best in vitro activity giving MICs 16of 1.56 mg/ml. Garlic had MICs of 0.97 mg/ml which was the best of all results. 17Lastly thyme had MICs of 15.6 mg/ml for the Mycoplasma gallisepticum. According 18to the results all Mycoplasma gallisepticum strains are sensitive to all antibiotics and 19plants extracts in different level and the highest effectiveness was for the garlic.